C−H Fluoromethoxylation of Arenes by Photoredox Catalysis. Issue 5 (27th December 2022) - Bertoli, Giulia; Martínez, Ángel Manu; Goebel, Jonas F.; Belmonte, Debora; Sivendran, Nardana; Gooßen, Lukas J.
Abstract: Redox‐active N ‐(fluoromethoxy)benzotriazoles were made accessible from fluoroacetic acid and hydroxybenzotriazoles via electrodecarboxylative coupling. After alkylation, they become effective monofluoromethoxylation reagents, enabling the photocatalytic C−H functionalization of arenes. Thus, irradiation of 1‐(OCH2 F)‐3‐Me‐6‐(CF3 )benzotriazolium triflate with blue LED light in the presence of [Ru(bpy)3 (PF6 )2 ] promotes the synthesis of diversely functionalized aryl monofluoromethyl ethers. This method allows the late‐stage functionalization of biologically relevant structures without relying on ecologically problematic halofluorocarbons. Abstract : A new class of [N−OCH2 F] redox‐active reagents were synthetized via electrodecarboxylative C(sp 3 )−O coupling of N ‐hydroxybenzotriazoles with fluoroacetic acid and subsequent alkylation. By irradiation with blue LEDs in the presence of a photosensitizer, these bench stable reagents allow the synthesis of monofluoromethyl aryl ethers via functionalization of C−H bonds.